WHAT IS RELATIONSHIP SATISFACTION? : EXAMINING RELATIONSHIP SATISFACTION AMONG MARRIED INDIVIDUALS USING CONFIRMATORY FACTOR ANALYSIS - Vajda, Karen (East Carolina University, 2015)
Marital satisfaction has been linked to numerous, important individual and couple outcomes including physical health, mental health, treatment of both physical and mental health disorders, work productivity, divorce rates, and general life satisfaction. To date, however, the research on marital satisfaction continues to employ a variety of conceptualizations and measurement techniques for this construct that make comparison across studies an often difficult task. Two of the most prominent theories regarding marital satisfaction have classified marital satisfaction as either a reflection of interpersonal processes and adjustment between spouses or as a reflection of subjective, intrapersonal feelings about one's marriage. The first research question addressed in this study, therefore, was to examine whether this conceptual division is reflected in the structure of marital satisfaction through the use of Confirmatory Factor Analyses (CFA). Additionally, marital satisfaction has often been shown to be highly related to, or predicted by, many other relational constructs including communication, commitment, quality time or couple bondedness, dominance, satisficing, and positive orientation towards the relationship. The second research question addressed in this study, therefore, was whether and how a number of common relational constructs fit into the structure of marital satisfaction as a construct. Data came from a statewide survey of Texan residents, the Texas Healthy Marriage Initiative Baseline Survey Project and included 1,528 married, heterosexual respondents. Results indicated that a bi-factor model with a single general construct of marital satisfaction was the best-fitting model for the data, indicating that shared variance across all items was best reflected as a distinct marital satisfaction construct. Within this model, associations among other relational constructs were smaller or reduced to non-significance in comparison to other models. Marital satisfaction, therefore, can be best conceptualized as an underlying common factor that accounts for some of the high overlap between relational constructs. Implications for clinicians working with married couples and directions for future research in this area are discussed.
Keywords: Quantitative psychology and psychometrics; Mental health; Adjustment; Marital satisfaction; Relationship quality; Psychometrics; Confirmatory factor analysis; Marital quality